Systematic search for structural motifs of peptide binding to double-stranded DNA - Kolchina, Nina (Nucleic Acids Res, 2019)
A large variety of short biologically active peptides possesses antioxidant, antibacterial, antitumour, anti-ageing and anti-inflammatory activity, involved in the regulation of neuro-immuno-endocrine system functions, cell apoptosis, proliferation and differentiation. Therefore, the mechanisms of their biological activity are attracting increasing attention not only in modern molecular biology, biochemistry and biophysics, but also in pharmacology and medicine. In this work, we systematically analysed the ability of dipeptides (all possible combinations of the 20 standard amino acids) to bind all possible combinations of tetra-nucleotides in the central part of dsDNA in the classic B-form using molecular docking and molecular dynamics. The vast majority of the dipeptides were found to be unable to bind dsDNA. However, we were able to identify 57 low-energy dipeptide complexes with peptide-dsDNA possessing high selectivity for DNA binding. The analysis of the dsDNA complexes with dipeptides with free and blocked N- and C-terminus showed that selective peptide binding to dsDNA can increase dramatically with the peptide length.